Network Access in the Deregulated European Electricity Market: Negotiated Third-Party Access vs. Single Buyer - Christoph Bier (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1999)
The question of third-party access to the networks has become central to the debate around the liberalisation of the European electricity markets due to the natural monopoly characteristic of the transmission network. The European Union?s electricity directive provides three institutional options for the organisation of network access: the single buyer procedure, the negotiated third-party access and the regulated third-party access. This paper analyses these regimes in a framework of an imperfect decision-making regulation authority which can commit errors when supervising the transmission tariffs. It will be shown that the equivalence of the systems required in the directive is usually not achieved. In addition, conditions for deciding between the three systems are derived under social welfare considerations. – – Bei der Liberalisierung der europäischen Elektrizitätsmärkte ist wegen der natürlichen Monopoleigenschaft des Übertragungsnetzes die Frage des Netzzugangs Dritter von zentraler Bedeutung. Die EU-Stromrichtline bietet drei institutionelle Alternativen zur Organisation des Netzzugangs an: Das Alleinkäufersystem, den regulierten und den verhandelten Netzzugang. Dieser Beitrag untersucht diese drei Netzzugangsregime im Kontext einer fehlerhaft entscheidenden Aufsichtsbehörde. Er kommt zu dem Ergebnis, daß die in der Richtlinie postulierte Ergebnisäquivalenz der Systeme in der Regel nicht erreicht wird. Darüberhinaus werden Kriterien für die Entscheidung zwischen den Alternativen unter Effizenzgesichtspunkten hergeleitet.
Keywords: L94; L43; K23; 330; Electricity Industry; Network Access; Imperfect Regulation Agency; Stromnetz; Netzzugang; Elektrizitätspolitik; Aufsichtsbehörde; Spieltheorie; Elektrizitätswirtschaft; Verhandlungstheorie; Theorie; EU-Staaten